Kontestasi dan Survivalisme Media Dakwah di Tengah Liberalisasi Industri Media: Analisis Media TV-9 Jawa Timur - Surokim, Surokim (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2019)
Local television has faced sharp contestation and interplay between actors and agents. As a proselytising TV, TV-9 has faced a dilemma between social functions and corporate functions. In this regard, as a da'wah media, it tends to uphold the religious social mission, while as a corporate media it is required to make a profit. This article is a critical study of how the contestation took place and how the survival of TV-9. The results of this study indicate that TV-9 has developed the concept of entertained da'wah in overcoming the contestation, namely da'wah as substance, while entertainment as the complement of the TV program. Additionally, TV-9 also tried to resonate the da'wah strategy with the cultural paths of the past and present that have existed within society.